IMPLEMENTASI PRIORITISASI PROYEK MELALUI EFISIENSI PENJADWALAN MENGGUNAKAN PROYEK CRASHING PADA LEMBAGA KEUANGAN XYZ - Kezia Tiurma Fedora Pasaribu (2023)
XYZ Financial Institution has a vision to become a leading digital institution. XYZ Financial Institution plans 33 application and technology development projects until 2025 as outlined in the 2025 Digital Innovation Plan. The number of projects is too much to make human resources who carry out application and technology development projects, the solution to the problem here must prioritize which one first to organize according to the criteria of need and urgency. The Weighted Scoring Decision Matrix and Value Effort methods will get prioritized project results. The results of the prioritized projects will later be processed by the CPM, PERT, and crashing methods due to delays in implementation. This research gets the final results of 5 priority projects, Proyek Pusat Informasi dan Helpdesk has a chance of project success estimated to be completed on time with the PERT method of 93.45% and the crashing duration is faster to 177 days, Proyek Jaringan Dokumen dan Informasi Hukum has a chance of success of 91.15% and the crashing duration is faster to 256 days, Proyek Website Lembaga has a 93.94% chance of success and a faster crashing duration to 58 days, Proyek Data Operasi dan Hasil Transaksi has a 91.15% chance and a faster crashing duration to 106 days, and the last Proyek Program Platform Internal has a 91.92% chance and a faster crashing duration to 147 days.